Nanobiotechnological obtaining of liposomal forms of antioxidant preparations based on bioflavonoids - Pylypenko, Daria; Prokhorov, Vitaliy; Dudnichenko, Olexander; Krasnopolsky, Yuriy (ScienceRise: Pharmaceutical Science, 2019)
Most pathological conditions are accompanied by lipid peroxidation and accumulation of oxidative stress products. The antioxidant action of natural hydrophobic compounds, such as quercetin, ubiquinone, curcumin, vitamin E, etc. is established. It is also known that these biologically active compounds act on different parts of antioxidant system. However, their use in parenteral drugs is difficult taking into account their hydrophobicity. Nanoparticles, such as liposomes, are used to increase the bioavailability of lipophilic antioxidants and to create water-soluble form of them. The aim of the work is to develop the liposomal preparation with co-encapsulation of two hydrophobic antioxidants, namely curcumin and quercetin. Methods. Technological methods of obtaining liposomes and analytical physicochemical, chromatographic (HPLC, TLC, GLC), methods of determination of particle size, pH were used. Results. As a result of the study, the formulation and technology of obtaining the liposomal form of curcumin and its composition with quercetin were proposed. The effect of fatty acid composition of lipids, the ratio “lipid: active substance" and the technological conditions on the liposomes formation and the level of encapsulation of active pharmaceutical ingredients were studied. The dependence of nanoparticle sizes on the pressure value and the number of homogenization cycles was investigated. The lyophilized product with a level of encapsulation of hydrophobic antioxidants at least 85 % was obtained. The physicochemical properties of the samples were observed. Conclusions. The technological scheme for obtaining of сomplex preparation containing curcumin and quercetin, involving the obtaining of lipid film, hydration of components, high-pressure homogenization, sterile filtration and lyophilization is proposed